Microbial Mechanistic Insight into the Role of Inulin in Improving Maternal Health in a Pregnant Sow Model - Zhou, Pan; Zhao, Yang; Zhang, Pan; Li, Yan; Gui, Taotao; Wang, Jun; Jin, Chao; Che, Lianqiang; Li, Jian; Lin, Yan; Xu, Shengyu; Feng, Bin; et al. (Frontiers in Microbiology, 2017)
General consumption of ‘western diet’ characterized by high refined carbohydrates, fat and energy intake has resulted in a global obesity epidemics and related metabolic disturbance even for pregnant women. Pregnancy process is accompanied by substantial hormonal, metabolic and immunological changes during which gut microbiota is also remarkably remodeled. Dietary fiber has been demonstrated to have a striking role in shifting the microbial composition so as to improve host metabolism and health in non-pregnant individuals. The present study was conducted to investigate effects of adding a soluble dietary fiber inulin (0 or 1.5%) to low- or high- fat (0 or 5% fat addition) gestational diet on maternal and neonatal health and fecal microbial composition in a sow model. Results showed that inulin addition decreased the gestational body weight gain and fat accumulation induced by fat addition. Circulating concentrations of pro-inflammatory cytokine IL-6, adipokine leptin and chemerin were decreased by inulin supplementation. Inulin addition remarkably reduced the average BMI of newborn piglets and the within litter BMI distributions (%) ranging between 17 and 20 kg/m2, and increased the BMI distribution ranging between 14 and 17 kg/m2. 16S rRNA gene sequencing of the V3-V4 region showed that fecal microbial changes at different taxonomic levels triggered by inulin addition predisposed the pregnant sow to be thinner and lower inflammatory. Meanwhile, fecal microbial composition was also profoundly altered by gestation stage with distinct changes occurring at perinatal period. Most representative volatile fatty acid (VFA) producing-related genera changed dramatically when reaching the perinatal period and varied degrees of increases were detected with inulin addition. Fecal VFA concentrations failed to show any significant effect with dietary intervention, however, were markedly increased at perinatal period. Our findings indicate that positive microbial changes resulted by 1.5 % soluble fiber inulin addition would possibly be the potential mechanisms under which maternal body weight, metabolic and inflammatory status and neonatal BMI were improved. Besides, distinct changes of microbial community at perinatal period indicated the mother sow is undergoing a catabolic state with increased energy loss and inflammation response at that period compared with other stages of gestation.